O problema da reduplicação do cotidiano na indústria cultural segundo Theodor Adorno - Guilherme Soares de Sousa (2016)
Our goal is to address the reduplication of empirical reality that the cultural industry manufactures in certain products according to conception of Theodor Adorno. We present the conception of the author on the cultural industry, highlighting how it produces goods geared towards a fun with uncritical distraction purposes, whose contents often would be a daily duplicate experienced by the people and which are conveyed the values and patterns of behavior and consumption that predominate in late capitalism. Our hypothesis is that the reduplication of empirical reality in audiovisual cultural goods expresses the use of technology within the cultural industry to achieve their goals, especially stimulate consumption and maintaining the current social situation. We will seek to show how the development of mass media and the mastery with their visual aids are applied in cultural goods provides a reality reproduction perfectly growing and how the world's duplicate would be used by the culture industry as an expedient to induce their consumers start to join, or even internalize the values and behavioral patterns aimed at consumption and served ideological purposes within their products.